2020
DOI: 10.21203/rs.3.rs-65547/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral changes before lockdown and decreased retail and recreation mobility during lockdown contributed most to controlling COVID-19 in Western countries

Abstract: BackgroundThe COVID-19 pandemic has prompted a lockdown in many countries to control the exponential spread of the SARS-CoV-2 virus, hereby reducing the time-varying basic reproduction number ( R t ) to below one. Governments are looking for evidence to balance the demand of their citizens to ease some of the restriction, against the fear of a second peak in infections. More details on the specific circumstances that promote exponential spread (i.e. R t > 1) are needed.MethodsIncidence data of cases and dea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Our findings suggest that increased visits to retail and recreation places, such as non-essentials shops, restaurants, and cinemas, might have contributed to the increased SARS-CoV-2 transmission nationwide; by comparison, essential visits to grocery and pharmacy stores were only associated with a small increase in transmission. Similar findings were reported by Deforche and colleagues, 13 who showed that decreased retail and recreation mobility contributed most to reduced COVID-19 epidemics in 35 high-income countries. These findings might justify the need to focus on non-essential recreation activities to reduce transmission.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings suggest that increased visits to retail and recreation places, such as non-essentials shops, restaurants, and cinemas, might have contributed to the increased SARS-CoV-2 transmission nationwide; by comparison, essential visits to grocery and pharmacy stores were only associated with a small increase in transmission. Similar findings were reported by Deforche and colleagues, 13 who showed that decreased retail and recreation mobility contributed most to reduced COVID-19 epidemics in 35 high-income countries. These findings might justify the need to focus on non-essential recreation activities to reduce transmission.…”
Section: Discussionsupporting
confidence: 88%
“…A UK-based modelling study [ 86 ] examined the effect of opening schools along with removing restrictions on different occupation groups and concluded increased transmission, i.e., R0 above one (the basic reproduction number, R0 is the average number of secondary infections produced by a typical case of an infection in a population where everyone is susceptible [ 12 ]). Continued restriction on recreational activities (e.g., restaurants and bars) during exiting has been suggested in a modelling study based in high-income countries [ 87 ].…”
Section: Resultsmentioning
confidence: 99%